Research in personnel and human resources management - Buckley, M. Ronald; Wheeler, Anthony R.; Baur, John E.; Halbesleben, Jonathon R. B. (Emerald Publishing Limited, 2020)
Research in Personnel and Human Resources Management serves as the premier annual series dedicated to the exploration of cutting-edge topics in the field of human resources management. This volume publishes theoretical and conceptual advancements in the field of human resources management related to leadership, the power of dyadic relationships in leadership development, ethical decision-making, prosocial advocacy for healthcare organizations, discrete incivility, mindfulness, and technological adaptations in employee selection.
Includes index.
Keywords: Personnel management.; Personnel management -- Research.; Business & Economics -- Human Resources & Personnel Management.; Personnel & human resources management.; elektronické knihy; electronic books